Effect of scour-blocker on a submarine pipeline - Zhang, Xiao Yue (2010)
Scour under submarine pipelines is a serious problem for industrial and environmental concerns. Hence, to search for a method to mitigate the extent of the scour is urgent. This report provides an approach that potentially can lower the possibility of the break of pipeline due to local scour by slowing down the scour propagation velocity. A device named scour-blocker is developed and expected to block the propagation of the scour hole. A series of experiment is conducted to test the effect of such a device. By comparing the scour propagation velocity for a pipeline with and without the use of the blocking device, two prominent findings are obtained: 1) The use of scour-blocker on the pipeline can stop the lateral propagation of a neighboring scour hole for a period of time compared to not using it. 2) The blocking time of a scour-blocker increases with its thickness, which means that how well the blocker functions to delay the scour propagation is very much related to the thickness of the blocker.